2013
DOI: 10.1521/psyc.2013.76.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Reflections on Suicide Among Soldiers

Abstract: This commentary considers the Nock et al. review article (this issue) and provides additional perspectives pertaining to current concerns about Soldier suicides. The review article is relevant to the current Army STARRS research project, which is one of the most significant scientific undertakings in the history of suicide research. The review is an outstanding and thorough consideration of psychosocial risk and protective factors that may be related to Soldier suicide. While Army STARRS is a landmark effort, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…In February 2015, a self-paced online training program, "Managing Suicide Risk Collaboratively: The CAMS Framework," was introduced and is currently being used in the U.S., Canada, Europe, Australia and Asia to improve competency, confidence and practice in suicide risk assessment, management and treatment. [57] Rosemarie Rizzo Parse is an inspirational frontrunner who set out to enhance the nursing profession through theory, research, education and practice. Her distinguished Human-Becoming Theory focuses on the client's quality of life and the principles of human dignity.…”
Section: Resultsmentioning
confidence: 99%
“…In February 2015, a self-paced online training program, "Managing Suicide Risk Collaboratively: The CAMS Framework," was introduced and is currently being used in the U.S., Canada, Europe, Australia and Asia to improve competency, confidence and practice in suicide risk assessment, management and treatment. [57] Rosemarie Rizzo Parse is an inspirational frontrunner who set out to enhance the nursing profession through theory, research, education and practice. Her distinguished Human-Becoming Theory focuses on the client's quality of life and the principles of human dignity.…”
Section: Resultsmentioning
confidence: 99%
“…There is no consensus on what makes suicide crisis intervention therapy effective (Thomas et al 2009 ). While most intervention models adhere to the same generalised structure (pre-therapy, therapy, post-therapy) the lack of detail provided on the content, progression, or protocol has resulted in the development and use of myriad models (Thomas and Leitner 2005 ), most of which have little or no empirical basis (Jobes 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thomas et al ( 2009 ) reported that most suicidal patients are treated with unproven therapies, a sentiment echoed by Jobes ( 2013 ) who commented on the ‘remarkably un-evolved and surprisingly limited’ knowledge of effective intervention models and concluded that many approaches used have ‘little to no empirical support’ (p.127). Models that have been forwarded face the same difficulty of the original structures and protocols – a clear structure but lack of detail that makes replication impossible.…”
Section: Introductionmentioning
confidence: 99%
“…Addressing the risk and resilience factors in solders can help identify interventions for all who suffer from suicidal thoughts and actions. Jobes's thoughtful commentary in this issue also informs us that creating a scientific legacy of understanding and evidence-based interventions may meaningfully address the military suicide prevention problem, with beneficial carryover effect for suicide prevention for the American public (Jobes, 2013).…”
Section: Robert J Ursanomentioning
confidence: 99%